Supply Chain Analysis of Nutmeg in North Maluku Province - Rusiana Rusiana; Siti Jahroh; Riskina Juwita (Jurnal Manajemen dan Agribisnis, 2025)
Background: North Maluku has been known worldwide as a nutmeg-producing area in Indonesia since the fifteenth century. The quality and potential aflatoxin issues that have become global issues certainly have an impact on the price of national nutmeg and North Maluku. Purpose: The purpose of the study was to analyze the supply chain and marketing margins by looking at the efficiency of nutmeg marketing in North Maluku. Design/methodology/approach: Using qualitative analysis and quantitative analysis. Determination of samples by purposive side and snowball sampling. Respondents numbered 110 people consisting of 100 farmers and 10 traders. Descriptive data processing, mathematical calculations of marketing margins, farmers' share, profit-to-cost ratios, and marketing efficiency. Findings/Result: The results of the study indicate that the nutmeg supply chain network in North Maluku has five marketing channels, many actors involved, and unstable prices so farmers' income is low as shown by the marketing margins and efficiency of more than < 50% for marketing dry nutmeg and dry mace. Marketing of nutmeg in marketing channel III, marketing margin of Rp 0 with Eps 55.189%. In marketing channel V, the margin is Rp 0 with Eps 68.112%. The marketing margin of mace in marketing channel III is Rp 0 with Eps 78.243%. The marketing margin of mace in marketing channel V is Rp 0 with Eps 60.061%. Marketing channels of nutmeg I, II, III, and IV are inefficient, and marketing of mace I, II, and IV is inefficient because Eps > 50%.Conclusion: Based on the analysis of profitable nutmeg marketing efficiency in channels III and V for marketing dry nutmeg seeds and channels III and V for marketing mace.Originality/value (State of the art): This study explains that supply chain analysis has a positive impact on increasing farmer income with farmer decision-making to market their crops directly without going through collectors. Marketing efficiency can be achieved if there are few actors involved, low marketing costs, and high farmers' share. Keywords: marketing margin, marketing efficiency, network chain supply, nutmeg, nutmeg marketing